68Ga-FAPI PET/CT for diagnostic accuracy and therapeutic response assessment in bleomycin-induced pulmonary fibrosis: an integrated preclinical study - Sun, Rui; Huang, Yilin; Deng, Hao; Wang, Qixin; Xiao, Canran; Guo, Chunmei; Wang, Tianyu; Liu, Lisheng; Hua, Jun; Chen, Xiaoliang (Frontiers in Medicine, 2025)
ObjectiveThis study aimed to assess the diagnostic and therapeutic monitoring potential of 68Ga-fibroblast-activating protein inhibitor (FAPI) positron emission tomography/computed tomography (PET/CT) in bleomycin-induced pulmonary fibrosis (BIPF).MethodsA preclinical model was established through intratracheal bleomycin administration (2 mg/kg) in C57BL/6 mice, with nintedanib treatment (50 mg/kg/day) initiated at day 28 post-modeling for longitudinal evaluation. Disease progression and therapeutic response were analyzed weekly over 5 weeks using 68Ga-FAPI-04 PET/CT, complemented by histopathological validation through fibroblast activation protein (FAP) immunohistochemistry.ResultsIn untreated fibrotic mice, 68Ga-FAPI-04 uptake demonstrated a progressive increase, peaking at 4w (SUVmean: Left lung: 0.68 ± 0.14; Right lung: 0.65 ± 0.18). Conversely, nintedanib-treated mice exhibited an unexpected elevation in tracer uptake during late-phase imaging, but SUVR showed a decrease than untreated.ConclusionThese findings underscore 68Ga-FAPI-04 PET/CT as a sensitive tool for non-invasive assessment of BIPF early diagnosis and progression. The observed discordance in tracer uptake patterns between treatment groups highlights the need for further investigation into the temporal dynamics of antifibrotic therapy response.